Fatal infection by Acinetobacter baumannii in Ramphastos toco (Muller, 1776) - Fernandes, Natália Coelho Couto de Azevedo; Zwarg, Ticiana; Garcia, Jamile Macedo; Ferreira-Machado, Eduardo; Takahashi, Juliana Possatto Fernandes; Landi, Marina Frota de Albuquerque; Peixoto, Melissa Prosperi; Guerra, Juliana Mariotti (Brazilian Journal of Veterinary Pathology, 2025)
Acinetobater baumannii is a critically important bacterial pathogen due to its multidrug resistance and association with severe clinical conditions, including septicemia. Its presence in animal hosts and environmental reservoirs underscores the importance of a One Health approach. We describe a fatal case of pneumonia, pericarditis, and aerosaculitis in a juvenile Ramphastos toco infected with A. baumannii, in Brazil. Postmortem examination revealed multifocal necrotizing lesions in the lungs and air sacs, with Gram-negative coccobacilli confirmed as A. baumannii via MALDI-TOF mass spectrometry. This report highlights the emerging threat of A. baumannii in wildlife populations and emphasizes the need for enhanced surveillance under a One Health framework.